A Change Management Training and Guidance for Gempita Berkarya Group, Banua Rantau Village, Batang Alai Selatan District, HST Regency - Mujenah; Arifin, Zainal; Artinah, Budi; Asiah, Antung Noor; Veronica, Pebrina; Novita, Cindy Lea (UrbanGreen Central Media, 2021)
The production of traditional cakes is now starting to decrease due to the presence of modern cakes and even imported cakes. It takes a lot of effort and help to revive the traditional cake which is a symbol of a region. The activities of providing counseling, motivation and change management to 20 traditional cake craftsmen in Hulu Sungai Tengah Regency provided benefits to help them dare to take important decisions in business,